Konsep Karakteristik Pendidik dan Peserta Didik Ideal dalam Tafsir Al-Qur’anul Adhim - Aisyah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
Teachers and students are two entities that cannot be separated in moving the dimensions of education, especially Islamic education. Both have continuous interactions that can result in intellectual encroachment, but in reality, some educators and students do not understand the concept of education, so educators have not been maximal in seeking the development of students' potential in accordance with the teachings of the Qur'an and Hadith. This study aims to determine the ideal character of educators and students contained in Surah al-Kahf verses 60-82, more specifically in the book of interpretation of the Qur'anul Adhim by Imam Ibn Kathir. This research was written using a literature study (Library Research) by reading and reviewing the literature that became the object of the research study. In addition, this study also refers to several works that discuss the characteristics that educators and students must possess in the modern era. This study concludes that someone who wants to study should convey his desire with full manners of courtesy, with determination and patience. Students must always respect the teacher and quickly apologize if they make mistakes. Teachers should try their best to explain the material presented so that students understand the intent and purpose of the material.